5-Aminosalicylic Acid Prevents Disease Behavior Progression and Intestinal Resection in Colonic and Ileocolonic Crohn's Disease Patients: A Retrospective Study. (10th August 2021) - Wan, Jian; Wang, Xuan; Zhang, Yujie; Xue, Xianmin; Li, Yani; Liu, Zhenzhen; Han, Shuang; Chen, Min; Nie, Yan; Shi, Yongquan; Liang, Jie; Wu, Kaichun
Abstract : Background and Aims . The efficacy of 5-aminosalicylic acid (5-ASA) in the long-term outcome of Crohn's disease (CD) patients was uncertain. This study aimed to evaluate the efficacy of the 5-ASA in preventing disease behavior progression and intestinal resection in CD patients. Methods . CD patients were prospectively enrolled from January 2008 to September 2019 in Xijing Hospital. Disease behavior progression was defined as the development of stricturing (B2) or penetrating disease (B3) in patients with nonstricturing/nonpenetrating disease (B1) at diagnosis. Cox regression analyses were used to investigate the associations between disease location progression, disease behavior progression, and intestinal resection and multiple covariates. Results . In total, 122 CD patients were followed up for 4.3 years. At the time of diagnosis, disease location was ileal in 19.7% (24/122), colonic in 41.0% (50/122), and ileocolonic in 39.3% (48/122). A total of 87 (71.3%) patients had B1 at diagnosis. The disease behavior progression and intestinal resection rates were 42.5% (37/87) and 29.5% (36/122). The use of 5-ASA reduced the risk of disease behavior progression (HR 0.30, 95% CI 0.14–0.61, P  = 0.001) and intestinal resection (HR 0.33, 95% CI 0.17–0.90, P  = 0.027) in colonic and ileocolonic CD patients. Patients who presented with ileal disease at diagnosis did not have the same protective effects when taking 5-ASA (P  > 0.05). Conclusions . The use of 5-ASA could improve the long-term outcome of CD patients with colon involvement. The result emphasized the importance of early use of 5-ASA in the daily management of colonic involved CD.